Maternal Depression, Parental Reflective Functioning, and Emotional Responses to Infant Crying: A Cross‐Sectional Study - Christine Firk (Mental Health Science)
ABSTRACT Maternal depressive symptoms are highly prevalent postpartum and have been shown to negatively impact maternal caregiving. The emotional response to infant crying has been shown to predict individual differences in the quality of caregiving behavior. Parental reflective functioning, that is, the ability to understand and reflect on the infant's mental states, may aid in understanding infant distress signals and thereby also regulating negative emotions in response to infant crying. Therefore, the first aim of the current study was to investigate differences in emotional responses to infant crying and parental reflective functioning in mothers with clinically relevant symptoms of depression compared to mothers without clinically relevant symptoms of depression and second to test whether an association between depressive symptoms and emotional responses to infant crying is mediated by parental reflective functioning. Mothers with infants between 1 and 12 months of age who participated in an online survey about the developing parent−infant relationship in Germany were included in the present study. Depressive symptoms, parental reflective functioning, and emotional responses to infant crying were assessed using the Patient Health Questionnaire (PHQ‐9), the Parental Reflective Functioning Questionnaire (PRFQ), and the My Emotions Questionnaire. A total of 25.1% (n = 148) of mothers reported clinically relevant depressive symptoms, whereas 74.9% (n = 441) reported no or only mild symptoms. Mothers with clinically relevant depressive symptoms showed increased emotional reactivity to infant crying and less optimal parental reflective functioning compared to mothers without clinically relevant depressive symptoms. Further, the association between maternal depressive symptoms and negative emotional responses like anxiety and frustration in response to infant crying was partly mediated by dimensions of parental reflective functioning. The findings indicate that the incorporation of parental reflective functioning in early parenting programs, particularly for mothers experiencing depressive symptoms or at risk for depression, may be a critical factor in promoting sensitive caregiving.